Metabolic Basis of Cognitive Improvement Associated With Active B Vitamin Supplementation in Cognitively Impaired Elderly Subjects – A Metabolomics Study - Zhou, Haiming; Wu, Yuanyuan; Jiang, Binhua; Li, Bowen; Li, Martin; Tian, He; Shui, Guanghou; Lam, Sin Man; Kwok, Timothy (Frontiers in Medicine, 2022)
Intervention studies with active B vitamins supplementation in cognitively impaired individuals have yielded varying results in randomized controlled trials. In addition, a negative interaction of active B vitamin supplementation with aspirin usage on cognitive outcome was noted, but the molecular basis of the interaction has largely remained unknown. To investigate the metabolic basis of cognitive improvement brought about by active B vitamin supplementation, we conducted an extensive metabolomics analysis covering 302 identified metabolites on the baseline and 24-month serum samples from a cohort of 137 subjects randomly assigned to active supplementation or placebo. Pathway analysis uncovered enhanced gluconeogenesis and War-burg effects underlying cognitive improvement in non-aspirin users supplemented with active B vitamins. In addition, metabolomics revealed that aspirin usage may interact with B vitamin supplementation by altering gut microbial metabolism, particularly in terms of propionate production. Lastly, our omics data suggest that varying capacities to assimilate B vitamins at baseline, possibly mediated by differences in gut microbial composition, may underlie variations in inter-individual responses to active B vitamin supplementation.